Gastroesophageal reflux: natural evolution, diagnostic approach and treatment - Hegar, Badriul; Vandenplas, Yvan (The Turkish Journal of Pediatrics, 2013)
Gastroesophageal reflux (GER) is a normal physiologic process occurring several times per day in healthy infants. Regurgitation is defined as the passage of refluxed gastric contents into the pharynx or mouth, sometimes with expulsion out of the mouth. There are only a few studies that have been performed to determine the prevalence of regurgitation and its natural course in infants, and some of them were cross-sectional and retrospective. However, evaluation of the natural evolution of GER becomes difficult, since the emergence of widespread self-treatment and/or therapeutic interventions. It is important to determine which children have GER disease to offer optimal treatment and to avoid costly and potentially invasive diagnostic testing. Symptoms due to GER are troublesome when they have an adverse effect on the well-being of the pediatric patient. In regurgitating infants, decreasing the amount of regurgitation is often seen by the parents as the most welcomed intervention that physicians can provide. Many medications have been attempted to overcome GER in infants, each with their own advantages and limitations.